2009
DOI: 10.1177/0731684408099924
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Dilatometric Properties of Carboxylated SWCNT/Epoxy Composites: Effects of the Dispersion in the Resin and in the Hardener

Abstract: In this study the effects of the dispersion of carboxylated single-walled carbon nanotubes (SWCNT-c) in epoxy matrices using two different routes were investigated. In the first route, SWCNT-c were dispersed in the resin using solvent and tip sonication. In the second route, SWCNT-c were dispersed in the hardener in two different ways: with and without solvent, but both with tip sonication. For comparison purposes, neat epoxy was also prepared using the same curing conditions. The samples were characterized vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…Furthermore, the use of surfactants or solvents to aid this process is still an open issue. A previous study 4 showed that significant increase in some mechanical properties is achieved by dispersing carboxylated SWCNTs in the hardener, indicating this to be a possible route for preparing nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of surfactants or solvents to aid this process is still an open issue. A previous study 4 showed that significant increase in some mechanical properties is achieved by dispersing carboxylated SWCNTs in the hardener, indicating this to be a possible route for preparing nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Only few works reported this procedure [2][3][4] . Gojny and Schulte 2 verified that the best dispersion was achieved by suspending the nanotubes in the hardener, followed by mild sonication, mixing with the epoxy resin, and an extra sonication step.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering profile of CNT powders is shown as comparison (a). The CNTs powders profile showed a knee-scattering feature corresponding to a size of about 6-8 nm, assessed as d = 2$/q [26,27]. Since the mean diameter of CNT was about 10 nm, it could be reasonably thought that this dimension corresponds to the cross-section of CNT when they were analysed vs. air, i.e.…”
Section: X-ray Analysis Of Nanocomposites Obtained By Direct Mixingmentioning
confidence: 99%
“…the spatial distribution of the nanotube filler within the matrix) plays a role in determining the nanocomposite mechanical modulus. Neat epoxy and nanocomposite samples were also tested by thermo-mechanical analyser (TMA) to evaluate the coefficient of thermal expansions (CTE), in both rubber and glassy regions [27]. Figure 11 shows the linear expansion dilatometric curves for the nanocomposite samples processed by direct mixing at isothermal temperature of 120°C along with the corresponding curve of neat epoxy system.…”
Section: Mechanical and Dilatometric Analysis Ofmentioning
confidence: 99%
“…CNTs are sheets of carbon atoms in a hexagonal arrangement, rolled to form a cylindrical tube, where the walls are constituted by single or multiple carbon atoms (MWCNTs) 1 . It is possible to find in open literature examples about the incorporation of carbon nanotubes into structural materials such as cement and polymers [1][2][3] . The addition of CNTs into composite matrices leads to significant changes of some aspects of their material properties.…”
Section: Introductionmentioning
confidence: 99%